Public Debt, Global Governance and Economic Dynamism - Paganetto, Luigi; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2013)
This volume presents a selection of contributions to the XXIV Villa Mondragone International Economic Seminar on (3z(BPublic debt, global governance and economic dynamism(3y(B. For the past 23 years, the Seminar has provided an ideal opportunity to meet and discuss the most topical issues in economic research. The quality of the scientific contributions and ensuing debates has consistently been outstanding owing to the participation of leading experts, and the most recent Seminar was no exception. The Seminar was held against the backdrop of high levels of public debt, especially in Europe, combined with very low growth in productivity. Furthermore, markets have been dominated by financial instability, raising the question of whether this is the result of the high debt levels or insufficient economic dynamism. Among the topics covered in this book are the economic challenges and growth policies in the United States; issues relating to the G20, global governance and regional integration; EU governance, growth and the Eurozone crisis; and EMU policy and public debt. Individual contributions also address the impact of labor market reforms, the need for sectoral rebalancing in the Euro area, fiscal multipliers and public debt dynamics, and the effects of fiscal shocks in Italy. The book concludes with a contribution on policy recommendations.s
Part I: US Growth Policies in the Election Year -- Part II: Assessing the Impact of Labor Market Reforms -- Part III: Imbalances, Tensions and Possible Readjustments: Evidence from Intertemporal Accounting and the Financial Accounts -- Part IV: G20, Global Governance and Regional Integration -- Part V: Multipliers, the Crisis and Beyond -- Part VI: EU Governance, Growth and the Eurozone Crisis -- Part VII: EMU Policy and Public Debt -- Part VIII: Policy Recommendations.
Keywords: Economics; Endogenous growth (Economics).; International economics; Macroeconomics; Economics/Management Science; International Economics; Macroeconomics/Monetary Economics; Economic Growth